VALIDITY OF PRODUCT ON THE DEVELOPMENT OF COMPASS, OBSERVATION, DEMONSTRATION, EVALUATION (CODE) TRAINING MODEL - Izwar lubis, Selamat Triono , Ambiyar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of this research was to measure the validity level of a product from the Compass, Observation, Demonstration, Evaluation (CODE) training model. Furthermore, this research was conducted using ADDIE steps. The instrument used to measure the model validity is a questionnaire through the validation sheet. Based on the validity test of the model development, it was obtained that the CODE training model book, Control System Training Module, Control System Training Module using CODE Model, Instructor Guide, and Learner Guide were declared valid, so they can be applied in training.